Sensory Characteristics of Various Concentrations of Phenolic Compounds Potentially Associated with Smoked Aroma in Foods - Wang, Hongwei; Chambers, Edgar, IV (My University, 2018)
This research describes the sensory odor characteristics of 19 phenolic compounds (11 phenol derivatives, six guaiacol derivatives, and two syringol derivatives) that have been associated with smoked aroma in previous literature. Seven concentrations varying from 1 to 100,000 ppm of each chemical were examined. A highly trained descriptive panel used a recently published lexicon for smoky aroma and flavor and found that smoked aroma compounds have many different attributes that make up smokiness. Musty/dusty, musty/earthy, pungent, acid, smoky, woody, burnt, ashy, cedar, creosote or petroleum-like collectively imparted smoked aroma. Most of the phenolic compounds were described as having smoky characteristics at low concentrations, generally at 1 and 10 ppm, except 3,4-dimethylphenol at 5000 ppm. 2,6-Dimethylphenol was not associated with smoky characteristics. This research is the first to evaluate a set of phenolic compounds for their sensory characteristics using a professionally developed set of sensory attributes.
Keywords: Phenolic; Odor; Smoked; Smoky; Sensory; Aroma